A PRODUCTION FACILITY LAYOUT REDESIGN WITH BLOCPLAN METHOD IN WATTAR KITCHEN OF AIR FORCE ACADEMY - Handayani, Limawati; Rahmah, Sermatutar Alya (Akademi Angkatan Udara, 2022)
Facility layout is the arrangement of machines, tools, buildings, operators, materials and others using certain algorithms with the aim of reducing the total cost of moving. The Cadet Care Kitchen, also known as the Wattar kitchen, is a kitchen where food is processed for consumption by Air Force Academy cadets. Youth nutrition must meet and exceed the food consumed. The cooking process in the Wattar Kitchen is divided into several rooms. It was found that the distance between the place for chopping vegetables and spices as well as the storage refrigerator was too far from the place for storing food ingredients. Based on these problems, this study made improvements to the layout using the Blocplan algorithm to minimize the distance of material moving from far away warehouses by chopping, becoming closer and more efficient.